2011
DOI: 10.3758/s13421-011-0084-1
|View full text |Cite
|
Sign up to set email alerts
|

The role of awareness in anticipation and recall performance in the Hebb repetition paradigm: implications for sequence learning

Abstract: Sequence learning has notably been studied using the Hebb repetition paradigm (Hebb, 1961) and the serial reaction time (SRT) task (Nissen & Bullemer, Cognitive Psychology 19:1-32, 1987). These two paradigms produce robust learning effects but differ with regard to the role of awareness: Awareness does not affect learning a repeated sequence in the Hebb repetition paradigm, as is evidenced by recall performance, whereas in the SRT task, awareness helps to anticipate the location of the next stimulus. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
37
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 33 publications
3
37
0
1
Order By: Relevance
“…Baddeley & Hitch, 1974;Baddeley, 2000), the Hebb repetition effect is not confined only to verbal stimuli. Indeed, it has been shown with, for example, visual (Horton, Hay, & Smyth, 2008;Page, Cumming, Norris, Hitch, & McNeil, 2006), visuo-spatial (Couture & Tremblay, 2006;Guérard, Saint-Aubin, Boucher, & Tremblay, 2011;Tremblay & Saint-Aubin, 2009;Turcotte, Gagnon, & Poirier, 2005), auditory-spatial (Parmentier, Maybery, Huitson & Jones, 2008;Lafond, Tremblay, & Parmentier, 2010), olfactory (Johnson, Cauchi, & Miles, 2013), and tactile (Johnson, Shaw, & Miles, 2016) stimuli. Furthermore, the range of stimuli demonstrating the Hebb repetition effect suggest that it is underpinned by a generalised characteristic of sequence learning, and not confined to storage in the phonological loop (Page et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Baddeley & Hitch, 1974;Baddeley, 2000), the Hebb repetition effect is not confined only to verbal stimuli. Indeed, it has been shown with, for example, visual (Horton, Hay, & Smyth, 2008;Page, Cumming, Norris, Hitch, & McNeil, 2006), visuo-spatial (Couture & Tremblay, 2006;Guérard, Saint-Aubin, Boucher, & Tremblay, 2011;Tremblay & Saint-Aubin, 2009;Turcotte, Gagnon, & Poirier, 2005), auditory-spatial (Parmentier, Maybery, Huitson & Jones, 2008;Lafond, Tremblay, & Parmentier, 2010), olfactory (Johnson, Cauchi, & Miles, 2013), and tactile (Johnson, Shaw, & Miles, 2016) stimuli. Furthermore, the range of stimuli demonstrating the Hebb repetition effect suggest that it is underpinned by a generalised characteristic of sequence learning, and not confined to storage in the phonological loop (Page et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…This is known as the Hebb repetition effect (Hebb, 1961). In the present study, we contrasted the typical condition involving a single repeated sequence with concurrent learning of 2 repeated sequences.…”
mentioning
confidence: 99%
“…In 1998, Baddeley, Gathercole, and Papagno (1998) suggested that working memory would be responsible for word learning. In this context, the Hebb repetition effect (Hebb, 1961) has been proposed as a good experimental analogue to word-form learning (Hitch, Flude, & Burgess, 2009;Mosse & Jarrold, 2008;Page, Cumming, Norris, McNeil, & Hitch, 2013;Page & Norris, 2009). Indeed, the Hebb repetition paradigm requires participants to memorize short sequences of items (e.g., digits) in their presentation order.…”
mentioning
confidence: 99%
See 2 more Smart Citations